TRANSLATION COMPETENCE IN THE PERUVIAN JOB MARKET: AN ANALYSIS OF TRANSLATION JOB ADVERTISEMENTS - AVILA MARIÑOS, KATHERINE; VELA AGUILAR, JUNETT; SAGASTEGUI TORIBIO, EDUARDO (LACCEI, 2025)
This study, situated within the framework of the Sustainable Development Goal (SDG) focused on quality education, examines how translation competence is introduced in job advertisements for translators in Peru, with the aim of identifying the most frequently demanded sub-competences. Employing a qualitative approach, the research adopts a case study design and applies content analysis to a sample of 100 translation job postings published on the most prominent digital employment platforms in Peru as well as an interview to a translation recruiter expert in order to corroborate and enrich the findings. This research is pivotal for improving university-level academic training, aligning with current labor market demands, and fostering the development and updating of key competences.